2005
DOI: 10.1021/la0501381
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of Nanoscale Structure of Polypeptide Multilayer Thin Films

Abstract: Multilayer thin films formed by sequential deposition of oppositely charged polypeptides on a charged surface are known from previous studies to comprise a mixture of types of secondary structure. Here, study of the perturbation of polypeptide film structure by deposition of poly(allylamine hydrochloride) (PAH) and poly(styrenesulfonate) (PSS) on the film surface has revealed differences in behavior attributable to physical properties of the peptides. The methods of analysis were circular dichroism spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(87 citation statements)
references
References 25 publications
3
83
1
Order By: Relevance
“…Techniques such as UV spectroscopy, circular dichroism spectroscopy, and FTIR are usually employed to determine the structural properties of the films. Several parameters will affect the secondary structure of the film's constituents, including the structural properties of the polyelectrolytes used for assembly [63][64][65] as well as solvent properties. As previously mentioned, this includes ionic strength, [61,66] pH, [61,66,67] type of solvent, [68] hydration, [69] and temperature.…”
Section: Secondary Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Techniques such as UV spectroscopy, circular dichroism spectroscopy, and FTIR are usually employed to determine the structural properties of the films. Several parameters will affect the secondary structure of the film's constituents, including the structural properties of the polyelectrolytes used for assembly [63][64][65] as well as solvent properties. As previously mentioned, this includes ionic strength, [61,66] pH, [61,66,67] type of solvent, [68] hydration, [69] and temperature.…”
Section: Secondary Structurementioning
confidence: 99%
“…As previously mentioned, this includes ionic strength, [61,66] pH, [61,66,67] type of solvent, [68] hydration, [69] and temperature. [67] Boulmedais et al [63] and Haynie and co-workers [64] showed, for example, that adding a (PSS/PAH) layer on top of a [PLL/poly(L-glutamic)acid; PLL/PGA) film significantly changed the secondary structure of the film. The changes were different depending on whether PSS or PAH was deposited first.…”
Section: Secondary Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Such crosslinks increase the stability of a peptide multilayer film. [27][28][29][30] The present proof-of-concept work concerns encapsulation of Hb with PLL and PLGA; designed polypeptides might be more useful for encapsulation and for in vivo application.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of enzymes by CD on solid surfaces is scarce in the literature [53]. Up to now, monitoring of structural changes after the adsorption A c c e p t e d M a n u s c r i p t onto solid surfaces is done by comparison of the spectra of free and immobilized peptides and proteins [17,54,55]. The similarity of both spectra is relevant, yet the best way to evaluate the correlation between a native and an immobilized protein structure is to calculate the secondary structure fractions (of -helix and -sheet) using standard algorithms [53].…”
Section: Enzyme Conformationmentioning
confidence: 99%